2023
DOI: 10.3390/cancers15030615
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Methylation Marker NRN1 plus TERT and FGFR3 Mutation Using Urine Sediment Enables the Detection of Urothelial Bladder Carcinoma

Abstract: Background: Aberrant DNA methylation is an early event during tumorigenesis. In the present study, we aimed to construct a methylation diagnostic tool using urine sediment for the detection of urothelial bladder carcinoma, and improved the diagnostic performance of the model by incorporating single-nucleotide polymorphism (SNP) sites. Methods: A three-stage analysis was carried out to construct the model and evaluate the diagnostic performance. In stage I, two small cohorts from Xiangya hospital were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Wei Ouyang 1 Ran Xu 2 Hanyu Yao 1 Shusuan Jiang 3 Qiang Lu 4 Cai Lv 5 Pei Li 6 Genming Xu 6 Jianye Liu 1 Long Wang…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Wei Ouyang 1 Ran Xu 2 Hanyu Yao 1 Shusuan Jiang 3 Qiang Lu 4 Cai Lv 5 Pei Li 6 Genming Xu 6 Jianye Liu 1 Long Wang…”
Section: F I G U R Ementioning
confidence: 99%
“…Our previous study showed that the methylation status of NRN1 exhibits remarkable performance in detecting urothelial carcinoma and can be used for its diagnosis. 2 , 3 In this prospective, multicenter study, we developed a novel risk‐stratification model based on urine biopsy to identify residual tumours after initial TURBT and to avoid unnecessary re‐TURBT procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As research in this area continues to progress, the integration of methylation markers and SNP sites into diagnostic protocols is poised to become a cornerstone of UBC management, offering renewed hope and improved care for patients affected by this challenging malignancy [34]. As the global population ages and environmental exposures continue to evolve, understanding the epidemiology, risk factors, and early detection strategies for bladder cancer becomes increasingly imperative [35].…”
Section: Advancements In Ubc Diagnostics Using Methylation Markersmentioning
confidence: 99%
“…Among urine-based diagnostic tests (UBDT), only urinary cytology is widely established in clinical practice, although it exhibits limited sensitivity in low-grade (LG) UCB and heavily relies on the expertise of the examiner [2]. Over the past two decades, several UBDTs have been developed in an effort to avoid unnecessary cystoscopies in the oncological follow-up of NMIBC patients without compromising patient safety [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Cystoscopic follow-up, in particular, is associated with significant discomfort for NMIBC patients and significantly contributes to the high long-term costs of this disease [18].…”
Section: Introductionmentioning
confidence: 99%